Aprendizaje contextualizado y expansivo: Una propuesta para dialogar con las incertidumbres en los procesos educativos - Rubio González, Juan; Gómez Francisco, Taeli (Universidad de Costa Rica, 2021)
Regarding the current context of pandemic, educational environments have been affected and stressed to the point of developing various crises and externalizing the real conditions of practices in educational centers. In this context, this critical scientific essay proposes the possibility of conducting a dialogue with uncertainties in educational processes, based on its contextualization and expansion. This implies considering the tensions / contradictions that are inherent to these complex and cultural-historical processes. In this sense, the problems of traditional teaching models were analyzed, based on certainties, prediction, and control, supported by a dualist and empiricist-positivist epistemic matrix, which entered into crisis during the pandemic. In addition, the need to dialogue with uncertainties in educational settings was arose, proposing the complexity and the historical-cultural approach as possible mediating paradigms of this process. To support the above, the main postulates of expansive and contextualized logics in educational processes were shown, as mechanisms that overcome certainties and promoters of educational contexts and practices that consider totalities, the material-social conditions of the cultural context, emergencies, chaos and diversity. It is concluded that the dualist epistemic matrix tends to weaken teaching-learning process and does not allow transformations, openings and dialogues with the new educational realities, attributes that contextualized and expansive educational processes do have, as they are heuristic proposals that allow understanding and managing complexity and the uncertainty of current scenarios.